(untitled) (The Journal of Building and Land Development, 2018)
This paper contributes to the discussion on revitalization of planning education in Africa. The source of data adopted a survey design which made use of data sources such as primary and secondary data, interviews with the professional body and other stakeholders. The paper reveals that there are many challenges facing planning education in Nigeria such as shortages of up-to-date books, lack of current journals, and cost of exposure to international conferences and workshops have unfortunately priced timely transfer of up-to-date knowledge out of reach of both lecturers and their students